Colonialism in Democracy: a Study of the State Budgeting Process in Sri Lanka - Abeysinghe, A.A.C. (My University, 2012)
This study explores the role of the state budgeting system in exerting control over utilization of resources in the delivery of services by state sector organizations. This research is based on the observation that state budgets are currently used merely to control public sector expenditure within limits approved by the Parliament. This concurs with the theoretical explanation on the budget’s role of resource allocation (Wildavsky 1975). However, this paper questions whether a state budget can operate neglecting its role of controlling the provision of public services using such resources. Currently, state budgets are prepared on PPBS (Planning, Programme, Budgeting System) approach and this paper argues that it is a good approach in allocating and controlling resource utilization in providing public services but in Sri Lanka, due to colonial legacies, the state budget deviates from the aspect of controlling public services, rendering the state budgeting practice merely a ritual. Data for this research are obtained mainly from the analysis of current and archival documents and semi-structured interviews. Data are analysed on the basis of Gramsci’s (1971) hegemonic analysis. Findings of this research are useful to policy makers in finding direction for improving budgetary control over public services and in enhancing the knowledge of accounting.